X‐Ray Diffraction and Mössbauer Spectroscopy Studies of Pressure‐Induced Phase Transitions in a Mixed‐Valence Trinuclear Iron Complex. Issue 28 (1st June 2016) - Madsen, Solveig R.; Gunnlaugsson, Haraldur P.; Moggach, Stephen A.; Eikeland, Espen; Wu, Lai‐Chin; Leupold, Olaf; Overgaard, Jacob; Iversen, Bo B.
Abstract: The mixed‐valence complex Fe3 O(cyanoacetate)6 (H2 O)3 (1 ) has been studied by single‐crystal X‐ray diffraction analysis at pressures up to 5.3(1) GPa and by (synchrotron) Mössbauer spectroscopy at pressures up to 8(1) GPa. Crystal structure refinements were possible up to 4.0(1) GPa. In this pressure range, 1 undergoes two pressure‐induced phase transitions. The first phase transition at around 3 GPa is isosymmetric and involves a 60° rotation of 50 % of the cyanoacetate ligands. The second phase transition at around 4 GPa reduces the symmetry from rhombohedral to triclinic. Mössbauer spectra show that the complex becomes partially valence‐trapped after the second phase transition. This sluggish pressure‐induced valence‐trapping is in contrast to the very abrupt valence‐trapping observed when compound1 is cooled from 130 to 120 K at ambient pressure. Abstract : Valence‐trapping in an Fe3 O complex : The effect of pressure on a mixed‐valence Fe complex has been investigated by means of single‐crystal X‐ray diffraction analysis (at up to 5.3 GPa), Mössbauer spectroscopy (under ambient conditions and at 4 GPa), and variable‐pressure synchrotron Mössbauer spectroscopy (SMS) at up to 8 GPa (see picture).